Neck pain burden in China and G20 countries: an analysis of 1990–2021 with a 30-year forecast for China - Li, Huale; Chang, Zhichun; Qin, Ting; Li, Yanfang; Hu, Mingren; Yang, Xinjing; Li, Jun; Xie, Yufeng (Frontiers in Public Health, 2025)
BackgroundNeck pain (NP) represents a significant global public health challenge and is the fourth leading cause of disability in China and among G20 nations. Given the accelerating trends of population ageing and shifts in contemporary lifestyles, the burden of NP is likely to increase, necessitating urgent, comprehensive analysis and the formulation of effective interventions.Objectives and methodsThis study utilizes the 2021 Global Burden of Disease (GBD) database to extract data concerning the incidence, prevalence, DALY rate, ASIR, ASPR, ASDR, and other relevant metrics of noncommunicable diseases in China and G20 countries from 1990 to 2021. The analysis is conducted via the R programming language, with joinpoint regression employed to calculate the APC and AAPC. Additionally, an ARIMA model is utilized to forecast the incidence rate in China over the next 30 years.ResultsIn 2021, China reported 10.29 million (95% UI: 8.06–13.03 million) incident cases and 48.37 million (37.66–60.06 million) prevalent cases of NP. The ASIR, ASPR, and ASDR were estimated at 567 (448–699) per 100,000 population, 2,549 (2,007–3,141) per 100,000 population, and 254 (166–357) per 100,000 population, respectively. Among G20 countries, NP affected 28.71 million (22.50–35.54 million) incident cases and 137.66 million (109.04–169.31 million) prevalent cases, with corresponding ASIR, ASPR, and ASDR values of 507 (398–617) per 100,000 population, 2,362 (1,856–2,892) per 100,000 population, and 234 (156–334) per 100,000 population, respectively. The analysis revealed no statistically significant changes in the AAPCs of the ASIR and ASPR for either China or the G20 countries from 19,902,021. Notably, women consistently presented higher ASIR and ASPR values than men did across all the studied populations. Projection models indicate that by 2051, NP incidence rates will remain stable for China and men, whereas women’s rates are anticipated to significantly decline.ConclusionThe global community must prioritize the burden of NP and promote precision diagnosis and prevention. Policies should balance technological innovation with social support, strengthen legislative protection for high-risk occupations and harsh climates, implement personalized interventions, and reduce the burden at its root.